"Negotiating nostalgia - gressive women’s memoirs in Urdu" - Noor, Farha (South Asian history and culture, 2021)
The Progressive Writers’ Movement (PWM) in India propagated an intellectual and cultural breakthrough, garnering significant debates regarding the status and roles of women. The Progressive Writers’ Association (PWA) along with the Indian Peoples’ Theatre Association (IPTA) created platforms for women to engage in political discussions, performing arts and literary activities. While important arguments were made regarding women’s engagements with the ‘literary’, there seems to be a gap in women’s narratives within the movement. After the decline of the PWM, a number of belated autobiographical works by women of the past Progressive circles were published. Two such narratives are Yad ki Rehguzar (2006) by Shaukat Kaifi and Hamsafar (1995) by Hameeda Raipuri. Recounting their lives in the company of progressive stalwarts, these autobiographies use a personal, nostalgic tone to narrate their participation in the progressive times. This paper aims to read the negotiations of nostalgia in these writings and explore their treatment of memory, genre and literary value.